2012
DOI: 10.1093/jjco/hys150
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Sentinel Lymph Node Metastasis and Validation Study of the MSKCC Nomogram in Breast Cancer Patients

Abstract: The risk factors for sentinel lymph node metastasis in our study were consistent with those in the Memorial Sloan-Kettering Cancer Center nomogram. The Memorial Sloan-Kettering Cancer Center nomogram is a useful tool that could accurately predict the probability of sentinel lymph node metastasis in our breast cancer patients. Axillary surgical staging might be avoided in patients with a predictive value of <16% and axillary lymph node dissection might be done directly in those with a predictive value >70%, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
40
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 26 publications
4
40
1
1
Order By: Relevance
“…Several nomograms, such as the MSKCC nomogram, have been developed to predict the likelihood of SLN metastasis only based on the clinicopathologic information including patient age, tumor size, tumor location, LVI, multifocality, histologic tumor type, etc. However, these nomograms and their following validation studies all failed to reach an AUC > 0.8 . In this study, we combined DCE‐MRI radiomic features with clinicopathologic characteristics to effectively improve the prediction performance, achieving a higher AUC of 0.869 on the independent validation set.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Several nomograms, such as the MSKCC nomogram, have been developed to predict the likelihood of SLN metastasis only based on the clinicopathologic information including patient age, tumor size, tumor location, LVI, multifocality, histologic tumor type, etc. However, these nomograms and their following validation studies all failed to reach an AUC > 0.8 . In this study, we combined DCE‐MRI radiomic features with clinicopathologic characteristics to effectively improve the prediction performance, achieving a higher AUC of 0.869 on the independent validation set.…”
Section: Discussionmentioning
confidence: 95%
“…However, these nomograms and their following validation studies all failed to reach an AUC > 0.8. [11][12][13][14][15][16][17][18] In this study, we combined DCE-MRI radiomic features with clinicopathologic characteristics to effectively improve the prediction performance, achieving a higher AUC of 0.869 on the independent validation set. The prediction performance slightly decreased (AUC = 0.836) when validation set features were generated using ROIs drawn by a second reader.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, Alran et al analyzed patients with SLN micrometastasis, but found no predictive value, with an AUC of 0.53 19. Even so, many research scholars still consider that MSKCC nomograms can be used to assess the risk of non-SLN metastasis and provide reliable prediction analysis 20,21…”
Section: Discussionmentioning
confidence: 99%
“…The aim of this study was to determine, in a large series of patients with primary invasive breast cancer treated initially by surgery, whether SWE findings could independently predict lymph node status when taking known predictors of nodal status such as invasive size, histological grade and vascular invasion status [ 11 , 12 ] into account. If SWE finding are predictive of lymph node involvement this may be clinically useful in selecting patients for neo-adjuvant chemotherapy (NACT), as the established predictors of nodal involvement are only definitively available post operatively, and ultrasound guided percutaneous biopsy of nodes with abnormal ultrasound morphology only establishes a diagnosis of nodal metastases in around 50 % of cases shown to be positive at surgery [ 13 ].…”
Section: Introductionmentioning
confidence: 99%